P202 Increase in diagnoses of early infectious syphilis: local outbreak or following the national trend?. (8th June 2017) - Goode, Deborah; Kennedy, Sarah; Evans, Amy; Talbot, Angela; Page, Emma; Cronin, Mary; Hughes, Gareth; Padfield, Simon
Abstract : Introduction: There has been a substantial increase in the incidence of early infectious syphilis (EIS) in our large city clinic, apparent since reconfiguration of services in July 2015. Methods: A retrospective case note review of electronic patient records was undertaken to investigate whether this was due to a local outbreak or in keeping with recent national trend. A database search for primary, secondary & early latent syphilis identified 78 and 116 cases in 2015 and 2016 respectively. These records were assessed using BASHH audit standards and reviewed for various lifestyle risk factors. We worked with Public Health England to address concerns regarding a possible local syphilis outbreak. Results: Of 168 patients, 85% were MSM: 34% and 28% were HIV positive in 2015 and 2016 respectively. Of the patients with known HIV, 64% were diagnosed as part of their HIV care. Partner notification reached 0.56 contacts per index case. Of the 89 contacts, over 50% were positive for syphilis. Retrospective analysis of surveillance data identified a breakpoint in July 2014 associated with a monthly increase in cases since then with no observable change in patient demographics. Discussion: Service reconfiguration focussed on MSM risk groups, coincided with increased EIS diagnoses within 1 year. However, epidemiological analyses indicate a continuum from 2014 following national trend. Routine syphilis screening in HIV care remains an essential tool for early case finding. As 80% were first syphilis infections we are evaluating syphilis point of care testing alongside capillary blood sampling to increase screening in outreach settings.